Digital Competence of Primary School Design and Technology Teachers for Online Learning and Facilitation: A Pilot Study - Go, C H; Rozali, M. Z. (Online Journal for TVET Practitioners, 2023)
This pilot study aimed to examine the reliability of the DIGIGLO Digital Competency Assessment instrument by using Cronbach's Alpha as a measurement of its reliability. The study involved 30 primary school Design and Technology teachers who held the position of Head of the Panel in the Batu Pahat district. Respondents answered an online questionnaire using Google Forms to provide the necessary data for this pilot study. The Statistical Package for Social Science (SPSS) software was used to analyze the data and obtain Cronbach's Alpha values. The analysis results showed that the Cronbach's Alpha values for the eight elements of digital competency ranged from .919 to .966. Therefore, the adapted DIGIGLO instrument is a valid and reliable tool for assessing teacher digital competencies.